FEMALE RESISTANCE AND JAVANESE CULTURAL SYMBOLISM IN THE MUSIC VIDEO 'LATHI' BY WEIRD GENIUS (FT. SARA FAJIRA) - Fathul Qorib; Aizun Najih; Ziya Ibrizah (Jurnal Komunikasi dan Kajian Media, 2024)
The use of traditional cultural elements in popular media tends to increase as it can attract audience attention. Similarly, in the music video "Lathi" by Weird Genius (ft. Sara Fajira), Javanese cultural elements are utilized in its visual narrative and lyrics. This study aims to analyze how Javanese culture is depicted in the "Lathi" music video using Ferdinand de Saussure's semiotic approach and Vincent Mosco's commodification theory. The method used is descriptive qualitative analysis of signs (signifiers) and meanings (signifieds) in eight selected scenes from the "Lathi" music video. The results show that Javanese cultural elements, such as wayang kulit, Jaipong dance, and Kuda Lumping, as well as the representation of Javanese women, are commodified to create a commercially appealing product. Furthermore, the video portrays women as initially weak and submissive to the whispers of men, yet as the narrative progresses, they rise and fight back, symbolizing strength and resilience. The use of cultural symbols not only enhances the aesthetic appeal but also amplifies the mythical and eerie impression of women when they decide to resist oppression. The conclusion of this study is that despite the commodification, the "Lathi" music video successfully introduces Javanese culture to a global audience and conveys important values about the strength and resilience of Javanese women in facing challenges.